Influence of multimodal low-opioid anesthesia on the dynamics of аnnexin V in blood plasma during cardiac surgery - S.R. Maruniak; O.A. Loskutov; O.M. Druzhyna; I.R. Malish; N.V. Korotchuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to analyze the effect of anesthesia on the dynamics of аnnexin V during coronary artery bypass grafting with сardiopulmonary bypass (CPB), and the dependence of direct clinical results on the expression of аnnexin V.